Central SBP and executive function in children and adolescents with primary and secondary hypertension. Issue 11 (November 2020) - Stabouli, Stella; Chrysaidou, Katerina; Kotsis, Vasilios; Chainoglou, Nancy; Chatzipapa, Nikoleta; Gidaris, Dimos; Zafeiriou, Dimitrios
Abstract : Objectives: The aims of the study were to assess executive function performance in children and adolescents with primary and secondary hypertension, and to investigate for associations with central SBP and ambulatory blood pressure. Methods: Forty-six pediatric patients with secondary hypertension because of kidney diseases and 46 patients with primary hypertension underwent ambulatory blood pressure monitoring, pulse wave analysis, and assessment of executive function using Behavior Rating Inventory of Executive Function. Results for comparisons are presented as mean (SD). Analysis of covariance was performed to examine the effect of blood pressure parameters and hypertension cause. Results: Patients with secondary hypertension had higher T scores in parent and self-reported Metacognition Indices compared with those with primary hypertension (51.2 ± 8.9 vs. 47.6 ± 7.5, P  = 0.05 and 49.6 ± 9.1 vs. 42.1 ± 7.9, P  = 0.001, respectively), but did not differ in Behavior Regulation Index T scores, as well as in mean arterial pressure z -score. Patients with secondary hypertension had higher central SBP z -scores ( P  = 0.05). Adjustment for central SBP attenuated differences in parent Metacognition Index between groups. Central SBP z -score associated with parent Metacognition ( B  = 0.95, 95% CI 0.02–1.87), Behavior Regulation ( B  = 1.14, 95% CI 0.07–2.21), and self-reported Metacognition Indices T scores ( B  = 1.48, 95% CI 0.39–2.56), independent of mean arterial pressure z -score, age, sex, socioeconomic status, hypertension cause, and antihypertensive treatment. Conclusion: Central SBP associates with executive function performance in youth with hypertension and could have complementary role to ambulatory blood pressure for identifying children at risk for adverse cognitive outcomes. Abstract : Supplemental Digital Content is available in the text